Insights of neurophysiology on unconscious state using combined transcranial magnetic stimulation and electroencephalography: A systematic review. (December 2021) - Arai, Naohiro; Nakanishi, Tomoya; Nakajima, Shinichiro; Li, Xuemei; Wada, Masataka; Daskalakis, Zafiris J.; Goodman, Michelle S.; Blumberger, Daniel M.; Mimura, Masaru; Noda, Yoshihiro
Highlights: TMS-EEG research on unconscious state was comprehensively reviewed. Some TMS-EEG neurophysiological indices could be useful biomarkers for unconscious state. Specifically, perturbational complexity index could be an applicable index for differentiating DOC. TMS-EEG may be a promising approach to examine unconscious state non-invasively. Abstract: Unconscious state has been investigated in numerous studies so far, but pathophysiology of this state is not fully understood. Recently, combined transcranial magnetic stimulation (TMS) and electroencephalography (EEG) has been developed to allow for non-invasive assessment of neurophysiology in the cerebral cortex. We conducted a systematic literature search for TMS-EEG studies on human unconscious state using PubMed with cross-reference and manual searches. The initial search yielded 137 articles, and 19 of them were identified as relevant, including one article found by manual search. This review included 10 studies for unresponsive wakefulness syndrome (UWS), 9 for minimally conscious states (MCS), 5 for medication-induced unconscious states, and 6 for natural non-rapid eye movement states. These studies analyzed TMS-evoked potential to calculate perturbational complexity index (PCI) and OFF-periods. In particular, PCI was found to be a potentially useful marker to differentiate between UWS and MCS. This review demonstrated that TMS-EEG could represent a promising neuroscientific tool to investigate various unconscious states. Further TMS-EEG research may help elucidate the neural basis of unconscious state.